Evaluation of Poly Acrylic Acid(PAA) Hydrogel Beads as Adsorbent for The Removal of Lead(II)ion from Water - Al- Abachi, Mouayad Q; Al- Awady, Nagam S; Al-Anbakey, Ahmed M (Al-Nahrain Journal of Science, 2013)
Laboratory studies reported earlier, have been showed a very promising result in the selective removal of heavy toxic metals from aqueous solution by a commercially available super absorbent polymer (SAP). In this study one of these super absorbent hydrogels (Poly acrylic acid) beads was used to remove Pb (II)ion from aqueous solutions. The effect of time on adsorption was studied. Kinetic experiments showed that the rate of Pb (II) adsorption on the hydrogel bead was quite good. More than, 90% of the equilibrium adsorption capacity occurs within (10hr) and the adsorption equilibrium could be achieved within (24hr), with adsorption equilibrium capacity (113.40 mg/g). The adsorption kinetic fit well with a pseudo-first-order equation. The effect of the initial metal concentration on the removal percentage of Pb (ll) ion was studied. Freundlich and Langmuir isotherm constants and correlation coefficients were calculated. The thermodynamic parameters G°, H°,S° and Hads were also calculated .